Sarcopenic Obesity in Cancer Patients: Focus on Pathogenesis - Wilson Matthew Raffaello; Andree Kurniawan (National Cancer Center - Dharmais Cancer Hospital, 2020)
Introduction: Sarcopenic obesity is an emerging problem in cancer patients. However, this is often difficult to diagnose without the measurement of body composition. Sarcopenic obesity is associated with increased mortality, chemo-toxicity, and other complications in cancer patients. Until now, there is scarce information about sarcopenic obesity in the cancer population.Method: We identified 1955 articles related to sarcopenic obesity in adult cancer patients using PubMed, PubMed Central, and Cochrane Library databases from January 1, 1989, until January 1, 2020. Firstly, we screened the titles and abstracts which mentioned sarcopenic and obesity, especially in pathogenesis. 29 articles could proceed to the next step; then, they were screened for the full text. All steps were reviewed by two authors.Results: At last, they were 9 articles included. Sarcopenic obesity is defined as the coexistence of sarcopenia and obesity, an increase in fat mass in the body. Sarcopenic obesity carried cumulative risks from each of the two individual body compositions. CT-scan offers the highest available precision in determining body composition parameters, especially in the cancer population. Multiple causes and interactions between hormonal changes, aging, disuse, neuronal, poor nutrition, physical inactivity, and low-grade inflammation played roles. Sarcopenic obesity is associated with chemotherapy toxicity. High protein intake should be initiated to ensure adequate protein intake. Resistance training is beneficial in improving muscle mass and strength by focusing on strength training, flexibility, and balance.Conclusions: Sarcopenic obesity is an emerging problem but is often neglected. Further research needs to be conducted especially in explaining the pathogenesis of sarcopenic obesity. The combination of physical exercise and diet modification is the best management to improve sarcopenia obesity in cancer patients.